Fiscal Sustainability and the Role of Inflation - António Afonso; José Alves; Oļegs Matvejevs; Oļegs Tkačevs (Center for Economic Studies and ifo Institute (CESifo), 2023)
We examine the relationship between inflation and fiscal sustainability with a two-step approach. In the first step, we estimate to estimate a country-specific time-varying measure of fiscal sustainability using the fiscal reaction function. This function captures the response of the primary balance to changes in the public debt ratio. In the second step, we examine how various measures of inflation such as headline inflation, core inflation, energy inflation, and food inflation affect the estimate of fiscal sustainability found previously. Our findings indicate that higher inflation rates contribute positively to the measure of fiscal sustainability, specifically through core inflation causing an improvement in fiscal sustainability, while the effect of energy inflation is conversely found to be negligible or even negative. These results imply that the initial burst of inflation caused by the energy price shock in 2021 probably did not help improve fiscal sustainability, whereas the subsequent high core inflation had a positive effect.
Keywords: C23; E31; E62; H50; H62; 330; fiscal sustainability; fiscal reaction function; time-varying coefficients; euro area; inflation; core inflation; panel data